The Hotel Sector as an Important Component of Regional Economic Infrastructure - NIKOLSKAYA, Elena Yurievna; PASKO, Olga Vladimirovna; ANIKINA, Elena Nikolaevna; DEKHTYAR, Galina Maxovna; LEBEDEV, Konstantin Anatol'evich (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).06, 2019)
This paper is focused on working out a set of areas for the development of the hotel sector as an important component of regional economic infrastructure. The authors establish that the hotel sector is expected to help achieve a set of objectives aimed at resolving existing social issues so as to ensure the well-being of the population and improving people’s standard of living, which include creating new jobs, improving the level and quality of service, boosting income levels for regions’ residents, and ensuring large inflows of foreign and domestic tourists. The paper identifies several unresolved macrolevel issues, including the lack of an integrated strategy for development and a relevant policy in the sector, the imperfect regulatory/legal framework, poor accounting in respect of economic entities, and the unsatisfactory level of quality of hotel services. The authors prove that at the microlevel the current key issues within the hotel sector include poor accommodation availability and the complicated economic conditions in which hotels get to operate these days.